Fostering Active Prolonged Engagement - Humphrey, Thomas, editor.
1 online resource
Keywords: "A must for exhibit developers, researchers, educators, and other museum professionals looking for ways to engage visitors more deeply with interactive science exhibits, this book documents the exploration and findings of the Exploratorium's Active Prolonged Engagement project, funded by the National Science Foundation. Both a significant contribution to visitor research and a nuts-and-bolts guide to exhibit development, Fostering Active Prolonged Engagement includes 15 APE Tales (exhibit recipes with photos, drawings, and detailed construction specifications); discussions of setting explicit goals for visitors' exhibit experiences; research and evaluation methods and results; and lessons learned for building constructivist-style exhibits."--Provided by publisher.